A Retrospective Case Series Analysis of the Relationship Between Phenylalanine: Tyrosine Ratio and Cerebral Glucose Metabolism in Classical Phenylketonuria and Hyperphenylalaninemia - McGinnity, Colm J.; Riaño Barros, Daniela A.; Guedj, Eric; Girard, Nadine; Symeon, Christopher; Walker, Helen; Barrington, Sally F.; Summers, Mary; Pitkanen, Mervi; Rahman, Yusof (Frontiers in Neuroscience, 2021)
We retrospectively examined the relationship between blood biomarkers, in particular the historical mean Phe:Tyr ratio, and cerebral glucose metabolism. We hypothesized that the historical mean phenylalanine to tyrosine (Phe:Tyr) ratio would be more predictive of cerebral glucose metabolism than the phenylalanine (Phe) level alone. We performed a retrospective case series analysis involving 11 adult phenylketonuria/hyperphenylalaninemia patients under the care of an Inherited Metabolic & Neuropsychiatry Clinic, collating casenote data from blood biochemistry, self-reported history of low Phe diet adherence, and clinical [18F]fluorodeoxyglucose positron emission tomography ([18F]FDG PET). The Phe:Tyr ratio was calculated for individual blood samples and summarized as historical mean Phe:Tyr ratio (Phe:Tyr) and historical standard deviation in Phe:Tyr ratio (SD-Phe:Tyr), for each patient. Visual analyses of [18F]FDG PET revealed heterogeneous patterns of glucose hypometabolism for eight patients. [18F]FDG PET standardized uptake was negatively correlated with Phe in a large cluster with peak localized to right superior parietal gyrus. Even larger clusters of negative correlation that encompassed most of the brain, with frontal peaks, were observed with Phe:Tyr, and SD-Phe:Tyr. Our case series analysis provides further evidence for the association between blood biomarkers, and cerebral glucose hypometabolism. Mean historical blood Phe:Tyr ratio, and its standard deviation over time, appear to be more indicative of global cerebral glucose metabolism in patients with neuropsychiatric symptoms than Phe.